Turning trash into treasure: An approach to the environmental assessment of waste prevention and its application to clothing and furniture in Switzerland. (3rd May 2022) - Wiprächtiger, Maja; Rapp, Martina; Hellweg, Stefanie; Shinde, Rhythima; Haupt, Melanie
Abstract: According to the waste hierarchy, waste prevention is environmentally superior to recycling or recovery, hence its inclusion in government policy. The assessment and prioritization of waste prevention strategies are impeded, inter alia, by ambiguous definitions and the lack of a sound environmental assessment method. In this study, a systematic approach to the environmental assessment of waste prevention activities (WPAs), covering the whole life cycle of products, was developed. The approach combines material flow analysis and life cycle assessment with a sustainable circular system design framework whilst giving special consideration to pivotal factors such as diffusion factor (share of population engaging in WPA), substitutability (degree to which a new product is replaced), effects on use‐phase impacts, and rebound effects. The application of the approach to the case studies of clothing and household furniture in Switzerland revealed lower impact saving potential than assumed initially, due to lack of participation, low substitutability, or high rebounds. For example, reusing clothing locally, instead of exporting it to low‐income countries, as currently done, displayed no or even negative impact savings since secondhand clothing in high‐income countries is often consumed in addition to new clothing. Drastic scenarios for clothes led to only moderate impact reductions of less than 15%, whereas a take‐back scheme for furniture reduced impacts by 70%. Concluding, the four factors (diffusion rate, substitutability, effects on use‐phase impacts, and rebounds) proved crucial in the assessment of waste prevention strategies and the approach presented was able to pinpoint improvement potentials of the waste prevention scenarios investigated.